Predictive factors of recurrence in spontaneous bacterial peritonitis in Tunisian patients with cirrhosis - Manel Moalla; Nour Elleuch; Wafa Dahmani; Aya Hammami; Wafa Ben Ameur; Aida Ben Slama; Ahlem Brahem; Salem Ajmi; Mehdi Ksiaa; Hanen Jaziri; Ali Jmaa (Future Science OA, 2023)
Introduction: Recurrent spontaneous bacterial peritonitis (SBP) in patients with cirrhosis is associated with poor prognosis. Aim: To assess the prevalence and the risk factors for recurrence and to evaluate its impact on the prognosis. Materials & methods: We conducted a retrospective study including patients with cirrhosis having a first episode of SBP. Results: A recurrence of SBP was identified in 43.4% of the patients who survived after a first episode of SBP. The mean time to onset of the first SBP recurrence from the first episode was 32 days. Recurrence factors were endoscopic hypertensive signs, a positive ascites culture, diarrhea and the MELD score. Conclusion: There was no impact on survival of recurrent SBP compared with the first SBP episode.